The historical genesis of the Dnipro football club in the first half of the 20th century - Stepanenko , Dmytro; Baldzhy , Ilona; Yakovenko , Artem; Grebenyuk , Oleg; Khadzhynov , Valeriy (Sportyvnyi Visnyk Prydniprovia, 2026)
Abstract: The article presents the results of a comprehensive scientific study on the historical stages of formation and evolution of the football club “Dnipro” during the first half of the 20th century. The relevance of the topic is determined by the significance of FC “Dnipro” as a socio-cultural phenomenon and a symbol of the sporting identity of the Pridniprovsky region. In the context of modern transformations in Ukrainian sports, studying the historical experience of establishing major sports institutions is critical for understanding the mechanisms of sustainable development in professional football. The aim of the work is to conduct a systematic analysis of the club's genesis, from amateur teams at the beginning of the century to the formation of a professional football structure. To achieve this goal, a complex of methods was used: historical-genetic, historical-comparative, the method of systems analysis, and source-based analysis of archival documents and the press. Special attention is paid to the method of oral history (interviewing) to clarify events of the recent period. The study reveals that the origins of football in Katerynoslav date back to 1911, and 1918 is identified as the official founding date of the club. The continuity of the team's development is traced through a series of transformations: from the collective of the Bryansk Workers' Industrial Technical School (BRIT) and the “Petrovets” team (of the Petrovsky plant) to the creation of the “Stal” voluntary sports society in 1936. The scientific novelty of the research lies in clarifying the chronology of the club's foundation and identifying a direct link between the “Alcor” amateur circle and subsequent professional generations of players. The development of infrastructure is analyzed in detail, specifically the construction of the “Stal” and “Metalurh” stadiums, as well as the influence of the region's industrial giants on the club's financial stability and human resources. Particular emphasis is placed on the post-war period of the team's restoration (1945–1949) and its transition under the patronage of the Ministry of Ferrous Metallurgy, which became the foundation for future successes on the all-union and international arenas. It is concluded that the evolution of FC "Dnipro" during the studied period is a classic example of the institutionalization of Soviet football, where the club functioned not only as a sporting unit but also as a powerful center for the social life of workers. It is proven that the team's success depended on the synergy of the city's industrial potential and the enthusiasm of the sporting community, which ultimately allowed for the formation of a unique “Dnipro” style of play.